Experimental investigation and characterization of laser welded NiTinol shape memory alloys. (January 2017) - T., Deepan Bharathi Kannan; P., Sathiya; T., Ramesh
Abstract: This article presents a study on ytterbium: yttrium aluminium garnet (Yb:YAG) laser welding of NiTinol sheet of 1 mm thickness. Bead on plate welding was made on NiTinol sheet based on Taguchi L9 experimental design. The input parameters considered for this work were welding speed, laser power, focal position and shielding gas blown distance. Argon shielding gas at a constant flow rate of 14 l/min was used to protect the weld from oxidation. The quality of the weld was investigated by studying bead geometry (bead width, depth of penetration), microstructure, microhardness and corrosion resistance. Weld with full penetration, better hardness and corrosion resistance than the base metal was obtained by this work.